In search of quasi-subordinate workers in China: A typology of gig riders by economic dependency and subordination. - Tu, Wei; Wang, Xueyu (International Labour Review, 2025)
The article focuses on identifying and classifying quasi-subordinate gig workers in China’s platform economy, specifically food-delivery riders, by examining their economic dependency and personal subordination. Using a large-scale survey of 7,680 gig riders across five Chinese cities and latent class analysis, the study finds that only about 19% fit the traditional binary employment framework as “employee-like,” while the remaining 81% constitute a heterogeneous “quasi-subordinate” category with varying degrees of economic dependency and subordination. High economic dependency correlates with longer working hours, greater work intensity, and increased perceived pressure, whereas high personal subordination is linked to lower job satisfaction; notably, social insurance coverage is inadequate among more subordinated subgroups. The study proposes context-specific, quantifiable indicators for identifying quasi-subordinate workers, contributing empirical evidence to support China’s emerging trichotomous employment status framework and offering insights relevant to global discussions on gig worker classification and protection.